Polyphasic approach using multilocus analyses supports the establishment of the new aerophytic cyanobacterial genus Pycnacronema (Coleofasciculaceae, Oscillatoriales) - Martins, Mariéllen Dornelles [UNESP]; Machado-de-Lima, Náthali Maria [UNESP]; Branco, Luis Henrique Zanini [UNESP] (Wiley, 2019)
A new Phormidium-like genus was found during an investigation of Oscillatoriales diversity in Brazil. Eight aerophytic populations from south and southeastern regions were isolated in monospecific cultures and submitted to polyphasic evaluation. The populations presented homogeneous morphology with straight trichomes, not attenuated, and apical cell with thickened cell wall. Phylogenetic analyses based on 16S rRNA gene sequences showed that these populations, plus the Brazilian strain Phomidium sp. B-Tom from GenBank, formed a highly supported and distinctive clade, which corresponds to the new genus Pycnacronema, comprising six new species: P. brasiliensis (type species), P. arboriculum, P. conicum, P. marmoreum, P. rubrum, and P. savannensis. These results were confirmed and supported by rpoC1 and rbcL genes evaluated independently and by the concatenated analysis of 16S rRNA, rpoC1 and rbcL genes (for all species but P. savannensis). Secondary structures of the D1-D1′, box-B, and V3 regions of the internal transcribed spacer were informative at specific level, being conserved in P. brasiliensis and variable among the other strains, also confirming the phylogenetic analyses. The generic name and specific epithets of the new taxa are proposed under the provisions of the International Code of Nomenclature of algae, fungi, and plants.
Keywords: 16S rRNA; 16S-23S ITS; Brazil; morphological evaluation; phylogenetic analysis; rbcL; rpoC1; taxonomy